Strategies to Reduce Urban Pollution Effects on Solar Panels: A Review - Bingying Zheng; Yihua Hu; Mohammed Alkahtani (Solar)
Urban soiling, consisting of dust, industrial byproducts, and other pollutants, presents a significant risk to the effectiveness and safety of solar energy systems. To achieve the goal of net zero, having renewable energy systems such as solar panels in urban environments can help. This review will examine the composition and variety of urban soiling and evaluate its impact on PV installation. The study will analyze the efficiency loss attributable to soiling, focusing on its impact on small-scale installations such as rooftops, building integrated photovoltaics (BIPVs), and large-scale urban solar installations. Furthermore, this study will also investigate various developing technologies and strategies to reduce the effects of urban soiling. This encompasses the examination of automated cleaning systems and robotic maintenance, with a specific focus on their potential effectiveness. This review aims to underline the importance of addressing urban soiling within the framework of sustainable urban development and the expansion of solar energy, with further research into the development of soiling mitigation technologies. Finally, soil management and further research gaps will be discussed.